The Effect of Corn Silk Ethanol Extract (Zea Mays. L) on Decreasing the Blood Glucose Levels - Dika Lukitaningtyas; I Ketut Sudiana; Abu Bakar (Alta Dharma Publisher, 2020)
Diabetes mellitus is a chronic metabolic complication that is serious and can cause an increase in world mortality rates. the efforts that have been made by the community are the use of complementary herbal therapies, namely Corn Silk. The study aimed at examining the effect of giving corn hair ethanol extract (Zea mays L) to decrease glucose levels. Methods: This study used a true-experimental, pre and post with a control group that was applied in this study. Eighteen mice tail samples were recruited using random allocation technique sampling and divided into two groups (interventions and control groups). Data analysis was performed and presented in descriptive statistics, and significant findings were computed using the paired t-test. Results: The results showed that the decrease in Glucose intervention group downhill from 144,33+11,543 to 137,78+5,740 after the intervention. Meanwhile, in the control group, the mean in Glucose increase from 134,00+10,124 to 153,78+7,412. The paired t-test obtained a p-value of 0.000, indicating that there were significant differences in the effect of giving corn hair ethanol extract (Zea mays L) to decrease glucose levels the intervention and the control group. Conclusion: Giving Corn Silk Ethanol Extract (Zea Mays L) can decrease Decrease Glucose Levels. Keywords: Corn Silk, Ethanol Extract, Glucose Levels.